Synthesis, Characterization and Primary Antimicrobial, Antifungal Activity Evaluation of Schiff bases of 4-Chloro-(3-substituted-phenylimino) - methyl-[2H] - chromene-2-one - Amit Kasabe; Vijay Mohite; Jayesh Ghodake; Jaydeep Vidhate (E-Journal of Chemistry)
Coumarins show promising antimicrobial and antifungal activity, this prompted to us to synthesize new derivatives of coumarins. 4-Chloro-2-oxo-2H-chromene-3-carbaldehyde was reacted with substituted aniline and rectified spirit to obtain a new series of Schiff bases of 4-chloro-(3-substituted-phenylimino) -methyl- [2H]-chromene-2-one (3a-i). Their structures were confirmed by IR, 1H NMR spectral data. The synthesized compounds were investigated for antimicrobial and antifungal activities. The data reported showed that the effect of variation in chemical structure was rather unpredictable. Seldom did a particular structural modification lead to uniform alteration in activity in all tests. The substitution which appeared to be most important for high order of activity in the number of test was the 3-chloro phenylimino group. The observed antimicrobial and antifungal activities are attributed to the substitution at rdposition of phenylimino moiety.